2021
DOI: 10.1111/nph.17688
|View full text |Cite
|
Sign up to set email alerts
|

Two evolutionarily duplicated domains individually and post‐transcriptionally control SWEET expression for phloem transport

Abstract: Summary Cell type‐specific gene expression is critical for the specialized functions within multicellular organisms. In Arabidopsis, SWEET11 and SWEET12 sugar transporters are specifically expressed in phloem parenchyma (PP) cells and are responsible for sucrose efflux from the PP, the first step of a two‐step apoplasmic phloem‐loading strategy that initiates the long‐distance transport of sugar from leaves to nonphotosynthetic sink tissues. However, we know nothing about what determines the PP cell‐specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 73 publications
0
22
0
Order By: Relevance
“…GA and sucrose functions are tightly interrelated and both are required for growth, therefore one may hypothesize that GA supplementation rescued the fertility of the sweet13;14 double mutant, though an indirect effect. Of note, many physiological studies have implied that Clade 3 SWEETs function in sucrose transport processes, and in all cases starch levels were impacted, including phloem loading in Arabidopsis and maize, seed filling in Arabidopsis and rice, and, notably, nectar secretion in Arabidopsis (28)(29)(30)(31)(32). In the case of phloem loading, the presence of SWEET11, 12 and 13 in the phloem parenchyma -the cell predicted to supply sucrose to the adjacent sieve element companion cell complex, which imports sucrose via the SUT H + /sucrose symporter -provides additional support for the physiological function in sucrose transport (33).…”
Section: Contribution Of Sweet13 In Sucrose Flow From Anther To Pollenmentioning
confidence: 99%
“…GA and sucrose functions are tightly interrelated and both are required for growth, therefore one may hypothesize that GA supplementation rescued the fertility of the sweet13;14 double mutant, though an indirect effect. Of note, many physiological studies have implied that Clade 3 SWEETs function in sucrose transport processes, and in all cases starch levels were impacted, including phloem loading in Arabidopsis and maize, seed filling in Arabidopsis and rice, and, notably, nectar secretion in Arabidopsis (28)(29)(30)(31)(32). In the case of phloem loading, the presence of SWEET11, 12 and 13 in the phloem parenchyma -the cell predicted to supply sucrose to the adjacent sieve element companion cell complex, which imports sucrose via the SUT H + /sucrose symporter -provides additional support for the physiological function in sucrose transport (33).…”
Section: Contribution Of Sweet13 In Sucrose Flow From Anther To Pollenmentioning
confidence: 99%
“…The CTD was highly non-conserved for AtSWEET11 and AtSWEET12 orthologs from different plant species ( Supplementary Figure 11 ). Recently, it has been shown that phloem parenchyma cell-specific expression of AtSWEET11 is regulated at the post-transcriptional level by the two evolutionary duplicated domains in the AtSWEET11 coding sequence along with its promoter including 5′ UTR through RNA-binding protein (Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The differential expression of AtSWEET11 and AtSWEET12 orthologs also support their specific roles in different plant species ( Supplementary Figure 8 ). Moreover, it has been shown that the phloem-specific expression of AtSWEET11 is controlled at post-transcriptional level (Zhang et al, 2021). More studies are needed to understand the regulation of these two transporters in controlling sugar availability to pathogens and in restricting disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded cross-sectioning was performed as described with minor modifications (Zhang et al ., 2021). GUS-stained samples of entire inflorescence from pSWEET13:SWEET13-GUS and pSWEET14:SWEET14-GUS plants were washed three times by PBS (pH 7.2) and fixed with cold 4% paraformaldehyde and 2.5 % sucrose buffer overnight.…”
Section: Methodsmentioning
confidence: 99%
“…More than 6 flowers at each stage were assayed for one repeat, and four independent repeats were conducted. For starch staining on wax embedded cross-sections, after stage 12 flower buds were fixed in Carnoy fixative overnight before moving to 70% ethanol, samples were dehydrated and embedded in wax as previously described (Zhang et al, 2021).…”
Section: Starch Staining Assaymentioning
confidence: 99%